TANGGUNGJAWAB HUKUM PELAKU USAHA TERHADAP PRODUK KOSMETIK BERBAHAYA DALAM MEWUJUDKAN PERLINDUNGAN KONSUMEN - Agustini, Sri; Siratni, Mia; Yoseva, Widya (Ensiklopedia of Journal, 2025)
Abstract: The circulation of hazardous cosmetic products containing high-risk chemicals poses a serious threat to consumers. This article examines the legal responsibilities of business actors in ensuring consumer protection based on Law No. 8 of 1999 on Consumer Protection. The study aims to analyze issues related to the violation of business actors' responsibilities, the effectiveness of government oversight, and legal remedies available to harmed consumers. The research adopts a normative juridical approach by analyzing relevant laws and real-life cases. The findings reveal that business actors are responsible for ensuring product safety, providing accurate information, and complying with licensing standards. However, weak government oversight and low consumer legal awareness remain major obstacles to law enforcement. This article highlights the importance of strengthening regulatory oversight and educating consumers to prevent the distribution of hazardous cosmetic products. Through collaboration between the government, business actors, and the public, effective consumer protection can be achieved.Keywords: Legal Responsibility, Hazardous Cosmetics, Consumer Protection.